Social media exposure and perception of drug use risks among undergraduates of University of Abuja (2022)
Several studies have established the role of social media in shaping young people's perception of issues such as self-esteem and body image. However, scant scholarly attention has been paid to social media exposure and perception of drug use risks among this cohort. Using the social cognitive theory, this study investigated the influence of social media exposure on perception of drug use risks among undergraduates of the University of Abuja. Survey and focus group discussion (FGD) were employed as research designs, while multi stage sampling procedure was used to select the samples for the study. A total of 340 respondents filled the questionnaire, while 7 discussants took part in each of the 8 sessions of the FGD. Quantitative data were analysed using descriptive and inferential statistics, while qualitative data were thematically analysed. Findings showed a correlation between social media usage and perception of drug use risks, as increased social media exposure led to perception of higher drug use risks and vice versa. Although majority of the respondents perceived drug use risks to be high, however they were undecided on the specific health consequences for users, especially youths. The study, therefore, recommends that relevant stakeholders, both governmental and non-governmental agencies should carry out aggressive advocacy and sensitization campaigns that would aim to educate the youths on the health consequences of drug use and the need to live drug free lives.